»What is Human?« Theological Encounters with Anthropology - Becker, Eve-Marie; Dietrich, Jan; Holm, Bo Kristian (Vandenhoeck & Ruprecht, 2016)
Already Scripture asks many questions regarding anthropological problems. In the 20th century, the scholarly field of anthropology has become a lot more complex heuristically, methodically and hermeneutically. Therefore, modern research needs to answer arisen questions considering a wide range of disciplines: Sociology, Philosophy, Ethics and also Empirical Research. This volume is an interdisciplinary project within theology. Contributions seek to not only reflect the state of the art in anthropological research from a theological point of view, but also provide a theological interpretation of one virulent question: What is a Human?
Keywords: Theologische Anthropologie; Aufsatzsammlung